CORONARY ARTERY BYPASS GRAFTING PORTENDS DECREASED RIGHT VENTRICUCULAR FUNCTION - Papestiev, Vasil; Jovev, Sasko; Sokarovski, Marjan; Andova, Valentina; Lazovski, Nikola; Mehmedovikj, Nadica; Zdraveski, Vangel; Grazhdani, Sonja; Ismail, Ljubica Georgievska (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
Decreased right ventricular (RV) function is a frequently observed phenomenon after coronary artery bypass grafting (CABG) that often implicated poor long term prognosis. The aim of this study was to assess the existence of RV dysfunction 4 to 6 months after CABG using echocardiographic Assessment of tricuspid annular plane systolic motion (TAPSE) and RV free wall longitudinal strain (RVFWS) using speckle tracking.During the period from October 2017 to October 2018, forty-seven consecutive patients undergoing CABG were enrolled in this prospective study. 2D transthoracic echocardiography was performed within one week before CABG as well as 4 to 6 months after surgery. All measurements were made by a single experienced investigator.4-6 months after CABG right atrial (RA) and RV dimensions were significantly increased although the mean value stayed in reference margins. TAPSE was significantly reduced (p=0.0001) as well as RVFWS (p=0.015) which showed fewer negative results implicating decrement in RV function after surgery. Patients with abnormal postoperative RVFWS had insignificantly larger preoperative end-diastolic and end-systolic volume index as well as worse left ventricular (LV) function manifested with lower LV ejection fraction (LVEF), lower systolic volume index (SVI) and more positive LV global longitudinal strain. We could not find any significant difference among preoperative values of RA and RV dimension as well as TAPSE and PAPs between patients with normal vs . abnormal postoperative RVFWS.Our study showed depressed RV function 4-6 months after CABG. We suggest that RV free wall strain could be obtained and should be applied along with other conventional markers in the assessment of RV function after CABG. Keywords: coronary artery bypass grafting, echocardiography, tricuspid annular plane systolic motion, right ventricular strain, right ventricular function.